Strategi Pemberdayaan Kelompok Wanita Tani Untuk Mewujudkan Pekarangan Pangan Lestari di Kabupaten Tana Toraja (Studi Kelompok Wanita Tani Kalolok Kelurahan Batupapan Kecamatan Makale Kabupaten Tana Toraja) - Damaris Rante; Syamsul Rahman; Awaluddin Yunus; Helda Ibrahim (Jurnal MeA (Media Agribisnis), 2026)
The Sustainable Food Yard (P2L) Program is a strategic initiative to enhance household food security while promoting women’s empowerment through the utilization of home gardens. Despite its potential, the implementation of this program still faces various challenges, particularly in Kalolok Village, Batupapan Subdistrict, Makale District, Tana Toraja Regency, which has distinct geographical and social conditions. This study employs a qualitative case study approach to explore in depth the empowerment process experienced by the Women Farmers Group (KWT) in implementing the P2L program. The research is descriptive-exploratory in nature, aiming to understand the dynamics, strategies, and challenges faced by the group. The findings indicate that the level of empowerment of KWT members is relatively high, as reflected in active participation in planning (72%), training (80%), mentoring (84%), and group deliberation (100%). Supporting factors include the availability of yard land (96%) and strong group cohesion (88%), while inhibiting factors consist of limited capital (68%), uneven technical knowledge (76%), unstable water supply during the dry season (52%), pest and disease attacks (64%), and limited market access (40%). The study also shows that the P2L program contributes to improved household food security, including increased availability of fresh vegetables (92%), reduced household food expenditure (88%), diversified food consumption (84%), and year-round food stability (88%). In addition, the program enhances household economic independence through savings, opportunities for product sales (76%), increased entrepreneurial motivation (80%), and improved welfare expectations (84%). Therefore, program sustainability should integrate P2L with micro-enterprise development and strengthen cross-sector collaboration in agriculture, cooperatives, and trade to maximize economic value added.